NILAI BUDAYA DALAM PERIBAHASA JEPANG - Trahutami, Sriwahyu Istana (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2011)
Universally every language in the world has proverbs. Proverb is one of language elements that inclined to be steady, not experience a change both from structure and meaning sides. Proverb is inherited hereditary. Proverb contains norms of social wisdom of the owner. Not only that, proverb also becomes guidance to do and has a long lasting relatively endurance. In the other worlds, Japanese proverbs are used to communicative every culture elements that Japanese has.